The Personal pronouns in the nominative case in Portuguese language textbooks: an analysis - Araújo, Alexandra; Neves, Cileya (Revista de Letras, 2024)
We investigated, from a sociofunctionalist perspective, the treatment given to personal pronouns in the nominative case in eleven collections of Portuguese Language Textbooks for the Final Years of Elementary School [6th to 9th Grade], approved by the National Textbook and Teaching Material Program (PNLD) (four-year period 2024-2027). We based our work on Labov (2008[1972]), Tarallo (2007), Castilho (2012), Neves (1997, 1999), Givón (1995, 2001), Tavares (2003), Görski and Tavares (2013). Each collection has four volumes, totaling forty-four. Of this total, we analyzed thirteen textbooks based on the elaboration of a script, which integrates the methodology. The results showed that most of the textbooks analyzed directly and/or indirectly address the teaching of personal pronouns in the nominative case, and we proposed some activities that contemplate their functioning, reflection and use in the communicative situation.